The Effect of Schadenfreude on Verbal Aggressiveness in Rival Manchester United Fans on Social Media Twitter - Bhima Lakhsetya Jati; Sugiyarta Stanislaus (Universitas Negeri Semarang, 2024)
Verbal aggression often arises when football fans witness the downfall of rival teams. A frequent phenomenon associated with verbal aggression is the relationship between Manchester United supporters and the fans of rival English Premier League clubs. This phenomenon is driven by feelings of schadenfreude, which can motivate football fans to express verbal aggression toward Manchester United fans. The purpose of this study is to investigate the influence of schadenfreude on verbal aggression among rival fans of Manchester United on Twitter. The research adopts a quantitative approach with a correlational design. The sampling technique employed is non probability sampling using convenience sampling. The study utilizes the schadenfreude scale and the verbal aggressiveness scale as instruments. The sample consists of 363 respondents, all of whom are Manchester United’s rival fans on Twitter. Data analysis was performed using simple linear regression, which resulted in an F value of 449.978 and a significance level of 0.000. Based on these findings, the hypothesis,